Structuring and Characterisation of the Medical Infusion set as emitter for Low-Cost Drip Irrigation System - Mofoke , A.L.E; Adewumi, J.K.; Mudiare, O.J.; Ramalan, A.A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2004)
The medical infusion set was re-structured to serve as a point source emitter for low-cost drip irrigation systems. The re-structured device, here referred to as ‘medi-emitter’, was subjected to laboratory tests to evaluate its hydraulic characteristics. A calibration experiment, relating flow rate and level of emitter opening, gave a discharge range of 0-533 lhr-1 as the emitter flow regulator was gradually opened to its maximum. The peak discharge of 533 lhr-1 was recorded under a pressure of only 49.05 kPa. This makes the medi-emitter particularly suitable for low-cost drip systems that operate under gravity flow with low pressures often less than 58.86 KPa. The exponent values of the emitter flow functions ranged from 0.610 to 1.038, thus characterising the device as a laminar emitter. The laminar characteristic increases progressively with closure of the flow regulator. Manufacturer’s coefficient of variation of the medi-emitter was 0.065. Measured coefficient of variation and deviation from nominal flow were between 5 and 19%. The energy head loss coefficient of the emitter ranged from 1.48 to 28.25, which is within the range of common water outlets widely in use. Discharge through the medi-emitter was found to increase with rise in water temperature, although these variations were insignificant at 95% probability level. The influence of temperature on discharge was stronger at lower levels of emitter opening. The emitter gave average soil wetting diameters of 0.679, 0.924 and 1.07 m for sand, loam and clay soils respectively, under a discharge of 2 lhr-1. These values are comparable to those of conventional emitters. Results from this research reveal the potential of the medical infusion set to adequately serve as emitter for low-cost drip irrigation systems, particularly because it is widely available even in most rural communities.